Pengaruh Daya Beli Masyarakat Terhadap Permintaan Ikan Malaja Di Kecamatan Tanggetada, Kabupaten Kolaka - Gazali, Muhammad; Ningsih, Neneng Rahayu; R, Muhammad Kadafi (Program Vokasi UNG, 2025)
This study aims to analyze the influence of consumers' purchasing power on the demand for Malaja fish in Tanggetada District, Kolaka Regency. The research employs a quantitative descriptive method with simple linear regression analysis. Data were collected through questionnaires distributed to 100 respondents who are consumers of Malaja fish. The independent variable is purchasing power, measured by income, while the dependent variable is demand, measured by purchase frequency and quantity. The results show a significant influence of purchasing power on demand, with a p-value of 0.012 (< 0.05). The coefficient of determination (R²) is 0.48, indicating that 48% of the variation in demand is explained by purchasing power. These findings highlight the important role of purchasing power, although other influencing factors remain unexamined